Gestión presupuestal y calidad de gasto público en la Municipalidad Provincial de Requena 2022 - Morillas Silva, Denisse Elda (2023)
The main purpose of this study was to identify the link between budget administration and the quality of public spending in the Provincial Municipality of Requena for the year 2022. With the purpose of obtaining the required data, an applied and non-experimental investigation was carried out. with a questionnaire made up of questions distributed among 152 workers. According to the results obtained, budget management qualifies as regular (25%); For its part, the quality of public spending is rated as regular by (23%). In short, it was determined that there is a considerable significant relationship between budget management and quality of public spending (r=0.664; p=0.000); Likewise, the annual commitment programming dimension presents an index and sig. of (rho of 0.667; p=0.000); For its part, the certification of the budget credit shows a coefficient and a sig. of (rho of 0.636; p=0.000); also budget execution a coefficient and a sig. of (rho of 0.507; p=0.000) and finally the budget modifications, a coefficient and a sig. of (rho of 0.574; p=0.000) both dimensions are significantly related to the quality of public spending in the Provincial Municipality of Requena 2022.